Preparation of Barium Sulfate Nanoparticles Using Semi-Batch Precipitation - Berenjian, A.; Ghasemi, M.R.; Zarghi, A. (Asian Journal of Chemistry, 2010)
The present work aims at the investigation of different aspects on the production of barium sulfate nanoparticles. The influence of different process control parameters such as the feeding rate, temperature and initial concentrations of the reactants on the particle size has been studied to gain a deeper understanding of the important controlling mechanisms in the formation of BaSO4 nanoparticles. The experiments were carried out via a simple precipitation reaction of sodium sulfate with barium chloride in a semi-batch reactor. Present results showed that the reaction temperature, molar ratio of Ba2+-SO42- (R) and presence of ethanol were the most important parameters for the size control of barium sulfate particles.